Food allergy spectrum in the tropic: clinical and epidemiological profiles in a colombian hospital. A cross-sectional study - Olaya-Hernandez, Manuela; Vasquez, Laura Del Mar; Silva, Diana Lucia; Martinez-Betancur, Sofia; Guerra, Maria; Arias, Oriana; Ramirez, Luis Fernando; Serrano, Carlos Daniel (Frontiers in Immunology, 2023)
Food allergy affects 2-10% of the general population; it is more frequent among children than among adults, and it is one of the leading causes of anaphylaxis.Diagnosis of food allergy requires a detailed medical history, skin tests, specific immunoglobulin E (IgE) tests for the food involved, and an oral challenge as final confirmation.This study aimed to describe the clinical and epidemiological characteristics of patients who underwent oral food challenges for suspected food allergies in a reference center in Colombia.